수중의 세슘처리를 위한 수처리 기술 동향 및 개선방안 - 정우창; 여우석; 이병락; 김종규 (한국수처리학회지, 25(5), 2017)
Cesium-137 is one of the most dangerous and ubiquitous radionuclides that has been released to the eco system and human being. Many treatment methods have been used to remove cesium particles, such as adsorption, ion exchange, filtration, coagulation and precipitation. Recently, various studies have been carried out using Prussian blue which has a high adsorption effect not only in the eco system but also on the removal of cesium absorbed in the human body. However, despite the excellent effect of removing cesium, Prussian blue has a disadvantage in separation and reuse due to its difficulty in recovering from water because of its high water-solubility characteristics. In order to overcome this disadvantage, a post-treatment process such as a separate filtration process or a secondary adsorption process is required, which is not efficient in terms of environmental and economic aspects. Recently, a research study combining a magnetic materials and Prussian blue showed that cesium particles in water were effectively removed. However, when the external magnetic field is present, the recovery rate is kept high, but the recovery rate is decreased due to the inability to magnetize itself. Therefore, if a super magnetic material having a magnetic force higher than that of a conventional magnetic material and a ferromagnetic material magnetizing itself after application of an external magnetic field are actively studied, it will be possible to effectively remove cesium from the water in an environmentally friendly and economical way. KCI Citation Count: 0